Experimental study of PID for attitude control of a quadcopter using an ESP32 - Moussaoui, Ahmed Khalil; Habbab, Mohamed; Abdeldjebar, Hazzab; Slimane, Hireche; Chandra, Ambrish; Gouabi, Hicham; Abdellah, Alhachemi Moulay (Institute of Advanced Engineering and Science, 2024)
Aerial robotics encompasses intricate kinematics and dynamics that govern the flight of quad-rotor systems. Among the various methods employed for flight control using microcontrollers like the ESP32 developed by ESPRESSIF; the proportional integral derivative (PID) controller stands out as a widely adopted approach. The ESP32 microcontroller offers a superior interface, delivering enhanced performance and response time, particularly in dynamic environments. This article delves into the implementation and viability of the ESP32 platform for communication with MATLAB/Simulink, as well as real-time data acquisition to control the attitude of quadcopter withe chassis F450. The PID controller was designed to specifically work with the ESP32 platform and rigorously tested on an actual quadcopter during flight operations. lastly, a comprehensive analysis of the data gained and empirical results from the physical model demonstrates that the proposed framework is effective.